Validity and Practicality of Electronic Student Worksheet (E-LKPD) Integrated with the Hands On Minds On Approach on Environmental Change Material to Train the Critical Thinking Skills of Grade X Senior High School Students - Deswita Ardyagarani; Herlina Fitrihidajati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
21st-century education requires students to possess critical thinking skills to face global challenges and solve problems effectively. In the context of biology learning, especially on environmental change material, these skills are essential and should be developed through innovative and interactive learning media. This study aims to develop an Electronic Student Worksheet (E-LKPD) integrated with the Hands On Minds On approach to enhance the critical thinking skills of Grade X students. The measured parameters include product validity and practicality. Validity was assessed based on content, language, and presentation, while practicality was evaluated through student responses and learning implementation, using critical thinking indicators such as interpretation, analysis, inference, evaluation, explanation, and self-regulation. The research employed a Research and Development (R&D) method using the 4D model: define, design, develop, and disseminate. The limited trial involved 34 students from Class X-10 at SMA Negeri 16 Surabaya. Data analysis was conducted using descriptive quantitative techniques by calculating percentages, implementation scores, and student response scores. The results showed that the developed E-LKPD achieved an average validity percentage of 98.15% (very good), an implementation score of 100% (very high), and a positive student response of 99.06% (very high). These results indicate that the E-LKPD integrated with the Hands On Minds On approach is feasible to be used as an innovative teaching material in biology learning, particularly in the environmental change topic.